2021
DOI: 10.1007/s13300-021-01105-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Lockdown on Metabolic Control and Access to Healthcare in People with Diabetes: the CONFI-DIAB Cross-Sectional Study

Abstract: Introduction:The COVID-19 pandemic led to an international health crisis and restrictions. While the phenotype associated with COVID-19 severity in people with diabetes has rapidly been explored, the impact of restrictive measures, including lockdown, and tertiary care disruption on metabolic control and access to healthcare remained unknown. The aim of our study was to provide a comprehensive assessment on the overall management of diabetes during lockdown, including glucose control, weight changes, health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
(42 reference statements)
2
23
1
Order By: Relevance
“…Eleven studies were included in the systematic review and meta-analysis. Three studies each were conducted in India [21,28,29] and Italy [14,22,23], while one each was conducted in France [24], Japan [25], Morocco [9], South Korea [27] and Turkey [26]. Six of these studies were retrospective, two each were prospective and cross sectional, while only one study was case control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies were included in the systematic review and meta-analysis. Three studies each were conducted in India [21,28,29] and Italy [14,22,23], while one each was conducted in France [24], Japan [25], Morocco [9], South Korea [27] and Turkey [26]. Six of these studies were retrospective, two each were prospective and cross sectional, while only one study was case control.…”
Section: Resultsmentioning
confidence: 99%
“…The domains assessed were overall bias, selection of the reported result, measurement of the outcome, missing outcome data, departures from intended exposures, classification of exposures, selection of participants into the study and bias due to confounding (Figure 2a,b). Seven studies [14,21,[24][25][26][27][28] showed low risk of bias in all the domains assessed, while three studies [22,23,29] were of concern in bias due to confounding. One study [9] was assessed as having high risk with respect to bias due to confounding and was graded as having high overall risk.…”
Section: Assessment Of Risk Of Bias In Included Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Governments have imposed interventions including isolation to contain viral transmission [ 18 ]. However, unintended consequences also have been observed, such as economic crises and deterioration of health behaviors [ 19 , 20 ]. These consequences may result in long-lasting effects on cardio-metabolic health [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological stress associated with measures to control the spread of COVID‐19, such as lockdowns, closures of schools, social distancing, and social isolation have been suggested to have a significant role in the onset, progression, and control of diabetes. 3 , 4 , 5 , 6 , 7 Moreover, compromised access to healthcare during the pandemic, as well as fears of risking infection by obtaining care, may lead to delayed diagnosis, delays in insulin and other treatments, more rapid progression of hyperglycaemia, and higher frequency of diabetic ketoacidosis (DKA) in children with newly diagnosed T1D, thus increasing the risk of morbidity, mortality, and burden on the healthcare system. 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%